Impact of invasive alien plants on understorey vegetation in Wayanad wildlife sanctuary - Vishnu Chandran, M (Department of Natural Resource Management College of Forestry, 2018)
The present study “Impact of invasive alien plants (IAP) on understorey vegetation in Wayanad Wildlife Sanctuary” was conducted in three vegetation types (Plantation, NF and Vayal) of WS II part of the sanctuary. The distribution characteristics of selected invasive alien species (IAPS) viz. Lantana camara L., Senna spectabilis (DC.) H.S. Irwin and R.C. Barneby and Chromolaena odorata (L.) R.M. King & H. Rob and the impact of these invasive alien species on the regeneration of other plant communities were studied and compared. L. camara and C. odorata invaded all areas of the sanctuary except in the borders of Kurichiat and Sulthan bathery forest ranges. Lantana invasion was high in the Kurichiat RF (Reserve forest) and Rampur RF. Chromolaena invasion was found to be high in Mavinahalla and Kurichiat RF. In WS II part of the sanctuary, S. spectabilis was mainly distributed along the boundaries of Sulthan bathery and Muthanga ranges. In Muthanga, Senna invasion was extended up to “Kakkapadam” (2.5 km from Muthanga station). Among the IAPS, Chromolaena showed the highest density in all the three vegetation types, while the density of Senna was lowest in all the three vegetation types in WS II area. The density of Chromolaena in plantation and NF was 4943.52 ± 1079.07 and 4996.47 ± 1484.42 respectively. The density of Lantana in plantation and NF was 322.35 ± 88.18 and 85.42 ± 29.55 respectively. The density of Senna in plantation and NF was 63.5 ± 31.66 and 49.74 ± 23.93 respectively. Senna invasion was absent in vayal. Vayal showed highest density of Chromolaena (5810.59 ± 1262.43). Chromolaena had the highest percentage cover in both plantation and vayal. In NF, Lantana has (14.2 ± 2.8) the highest percentage cover. In all the three vegetation types, Chromolaena had the highest frequency and abundance. Among the seven weed category areas identified from the study area, highest MSR (Mean Species Richness) was seen in Control (weed free area), followed by L (Lantana invaded) and LC (Lantana and Chromolaena invaded)regions. The lowest MSR was obtained in S (Senna invaded) and CS (Chromolaena and Senna invaded) regions. All the three IAPS negatively influenced the native species richness. But no specific declining trend in species richness was observed during regression analysis. Results of regression analysis showed that, among the three IAPS, C. odorata had the biggest impact on the species richness of native species. It was followed by L. camara and S. spectabilis. Species richness of each growth form (herb & shrub) declined significantly with increasing Lantana, Chromolaena and Senna cover. In the current study, trees and climbers did not show any significant variation with increasing percentage covers of IAPS. For every 10% increase in percentage cover of C. odorata, two native herb species were observed being removed from the study area. At the same time only one shrub species was removed at every 10% increase in Chromolaena cover. For every 10% increase in Lantana cover, one native herb species was removed from the study area of the sanctuary. The species richness of shrubs also declined due to Lantana invasion. On plotting herb species richness against Senna percentage cover, only four herb species were obtained at 50% Senna cover. On further increase in percentage cover of Senna the herb species richness declined linearly and it was decreased to one at 100% Senna cover. It was also found during the study that, in plots where Senna and Chromolaena occured together, the species richness decreased from 86 to 4. Similarly in plots where Senna occured with Lantana and Chromolaena, species richness declined. This probably indicates a dominating interference of Senna on the recruitment of native species and could be because of the impacts of its larger size, big and wider canopy, competitive reproductive ability, allelopathy and a broad, deeper root system. Out of the 125 plant species identified from the sanctuary, only thirteen were observed from Senna invaded region. But during regression analysis it was found that, among the three IAPS Senna has the least impact on native species richness. This may be due to the fact that compared with Lantana and Chromolaena, the invasion of Senna is restricted to only a small portion of Wayanad WLS. But left uncontrolled Senna will soon become a major threat in Wayanad WLS in the near future.